Severe Agranulocytosis following Simultaneous Administration of Chlorpromazine and Trimethoprim-Sulfamethoxazole in a Patient with Sepsis: A Possible Toxic Combination - Anil Jha; Hassan Ghoz; Nicholas James (Case Reports in Medicine)
Background. Chlorpromazine and trimethoprim-sulfamethoxazole (TMP/SMX) are two commonly prescribed medications by physicians. Either of those medications could cause fatal drug-induced agranulocytosis, with an unclear underlying mechanism. The likelihood of simultaneous prescription of both medications is high and could hypothetically result in severe agranulocytosis that is resistant to treatment. Case Presentation. We are presenting a case of a patient with psychosis on chlorpromazine who was prescribed TMP/SMX for a urinary tract infection. Consequently, the patient developed severe agranulocytosis and septicemia. Patient was managed by granulocyte colony-stimulating factor; however, the time to neutrophil recovery was delayed when compared to the average reported time published by previous studies. Conclusions. Simultaneous use of chlorpromazine and TMP/SMX is a possible toxic combination that could induce severe agranulocytosis. Further reports are needed to confirm this observation.